Dizziness in an older community dwelling population: A multifactorial syndrome - Gaßmann, Karl-Günter; Rupprecht, Roland (Journal of Nutrition, Health & Aging, 2009)
Objectives: The aim of this study was to determine the prevalence and related predictors of dizziness in a sample of community-dwelling people 65 years of age and older living in a metropolitan area in Germany. Design: Prospective cohort study. Setting: Interdisciplinary Centre of Gerontology at the University of Erlangen-Nuremberg, Germany. Participants: 6000 people aged 65 years and older recruited and randomized from the registration office, 1801 were fully evaluated at baseline and were re-evaluated in a prospective follow-up two years later. A full data set was obtained for 620 participants, of which 297 (47.9%) were females. Mean age was 73.45 ± 6.05. 200 participants (32.4%) were 65-69 years, 315 (51%) were 70-79 years, 92 (14.9%) 80-89 years and 11 (1.8%) 90 years and older. Measurements: Demographic, medical, functional and psychological factors were measured by a standardised questionnaire in 2004. In a follow-up survey participants were reevaluated in a prospective design two years later (2006), including a dizziness questionnaire, containing frequency, duration, space of dizziness and releasing positions and activities. Results: At the second measurement 181 persons (29.2%) reported dizziness in the last 6 months. Dizziness was age dependent, with a prevalence of 27% in participants aged 70 years and younger, up to 54% in the group of 90 years and older. 96 (68.2%) persons reported daily or weekly dizziness. 46 (27.9%) participants reported multiple sensations of dizziness. In 108 (59.7) persons dizziness was released by multiple positions or activities. The main predictors of dizziness were age, female gender, cardiovascular disease, osteoporosis, depression, sleep disorder, disturbance of memory, shortsightedness (defined by glasses), incontinence, 3 and more medical conditions, 4 and more medications, poor health status, falls and mobility problems. We found similar risk factors for dizziness and falls. Conclusion: Dizziness is a very common symptom in older community dwelling persons. Comorbidity, poor health status and mobility problems are strong medical predictors; age and female gender and decline in mobility are important predictors as well. Our study suggests, that dizziness in older age is often caused by multifactorial medical and functional conditions. Gait disorders and mobility problems also seem to play an important role in dizziness among older people. Therefore, interventions in dizziness should be developed in a multifactorial way. We suggest, that the interventions to be tested first, should be those that have been previously successful in older persons with gait disorders and falls.